2018
DOI: 10.3389/fphar.2018.00656
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Led Intervention to Enhance Medication Adherence in Patients With Acute Coronary Syndrome in Vietnam: A Randomized Controlled Trial

Abstract: Background: Patient adherence to cardioprotective medications improves outcomes of acute coronary syndrome (ACS), but few adherence-enhancing interventions have been tested in low-income and middle-income countries.Objectives: We aimed to assess whether a pharmacist-led intervention enhances medication adherence in patients with ACS and reduces mortality and hospital readmission.Methods: We conducted a randomized controlled trial in Vietnam. Patients with ACS were recruited, randomized to the intervention or u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 38 publications
2
35
0
4
Order By: Relevance
“…The current study has shown that pharmacist led intervention through patient education and follow up has considerable impact on optimizing patient' medication adherence as evidenced by the finding that 63.3% of the patients in intervention group had high level of adherence compared to only 21.1% of controls. This finding is in accordance with a randomized controlled trial done in Vietnam which revealed that pharmacist interventional program via patient education caused remarkable enhancement in adherence to ACS discharge medications [26] . In United States, a randomized controlled trial revealed that pharmacist multifaceted intervention consisting of patient education and follow up by phone calls and voice messages increased medication adherence markedly among patients with ACS [35] .…”
Section: Discussionsupporting
confidence: 91%
“…The current study has shown that pharmacist led intervention through patient education and follow up has considerable impact on optimizing patient' medication adherence as evidenced by the finding that 63.3% of the patients in intervention group had high level of adherence compared to only 21.1% of controls. This finding is in accordance with a randomized controlled trial done in Vietnam which revealed that pharmacist interventional program via patient education caused remarkable enhancement in adherence to ACS discharge medications [26] . In United States, a randomized controlled trial revealed that pharmacist multifaceted intervention consisting of patient education and follow up by phone calls and voice messages increased medication adherence markedly among patients with ACS [35] .…”
Section: Discussionsupporting
confidence: 91%
“…Because of the intervention, content in randomized clinical trials was focused on counselling on medications use and the importance of adherence to medication. 15 These contents were little or not relevant to the surveyed knowledge in our questionnaire. Otherwise, the patients of the intervention group were consulted on using medications whereas our questionnaire asked about the mechanism of medications (for example, question 11 asked about the mechanism action of statins).…”
Section: Discussionmentioning
confidence: 97%
“…This study raises questions about the effectiveness of pharmacist intervention in the management of CHD. While some studies have shown positive effects of pharmacist intervention on medication adherence and lipid management in CHD patients (Faulkner et al, 2000; Straka et al, 2005; Ho et al, 2014; Nguyen et al, 2018), there is heterogeneity in the results (Community Pharmacy Medicines Management Project Evaluation Team, 2007; Calvert et al, 2012; Schwalm et al, 2015). So far, the number of studies evaluating the contribution from pharmacists in the management of CHD is small, and most of these studies included a limited number of participants; it is necessary to conduct further studies to confirm the role of pharmacists in the secondary prevention of CHD.…”
Section: Discussionmentioning
confidence: 99%